Admission criteria for MBA programs : a review (2016)
This paper reports a review of studies on admission criteria for MBA programs. The method consisted in a literary review based on a systematic search in international databases (Emerald, ABI/INFORM Global, ProQuest Education Journals, ProQuest European Business, ProQuest Science Journal, ProQuest Research Library, ProQuest Psychology Journals, ProQuest Social Science Journals and Business Source Complete) of studies published from January 1990 to December 2013, which explore the academic performance of students or graduates of MBA programs. A quantitative review was performed. Results show that most researchers studied relations between GMAT (Graduate Management Admission Test) and UGPA (Undergraduate Grade Point Average) as predictors of GGPA (Graduate Grade Point Average). On the other hand, work experience and personal traits (such as personality, motivation, learning strategies, self-efficacy beliefs and achievement expectations) and their relation with GGPA had been less studied, and results are not consistent enough to consider them valid predictors of student performance at this time.